Investigations Selected Influencing of Process Factors for Transient Liquid Phase Soldering (TLPS) as a Die-attach Method for Automotive Power Modules - Ottinger, Bettina; Holverscheid, Joshua; König, Sebastian; Brunner, Annette; Müller, Lars; Goth, Christian; Franke, Jörg (Advancing Microelectronics, 2024)
Increasing the operating temperatures in power electronic applications cause a decreasing lifetime of the die-attach interconnection. Transient liquid phase soldering (TLPS) is able to create a reliable and high temperature resistant connection layer via diffusion processes in the form of intermetallic phases with melting points up to > 400°C. This study concentrates on a TLPS reflow-soldering process with a tin-copper-tin (Sn-Cu-Sn) layered preform. During the soldering process the influence of the selected process parameters for the Sn-Cu-Sn on the grown intermetallic phase interconnections between the preform and the components are investigated via the average void percentage and a process capability analysis (cpK). The application of mechanical pressure decreases the average void percentage below 10%. Due to the lower average void percentage the influence of the holding time, peak temperature and heating gradient are examined under low pressure. The biggest impact shows the heating gradient. With a slow heating gradient, the thermomechanical stress decreases by increasing the solubility and the average void percentage could be reduced to less than 2.7 %. In combination of the optimized selected process factors it is possible to reach a process capability value of 1.
CRIS-Team Scopus Importer:2024-05-31
Keywords: automotive power module; die-attach; reflow-soldering process; Sn-Cu-Sn; thin solder layers; TLPS